The Combined Effectiveness of Debridement and Vacuum-Asisted Closure (VAC) Method in the Management of Diabetic Foot (Annals of Medical Research, 2021)
None
Keywords: Diabetic Foot; Vacuum-Assisted Closure; Debridement.